Effect of ambient air pollution exposure on renal dysfunction among hospitalized patients in Shanghai, China. (April 2020) - Wang, W.; Wu, C.; Mu, Z.; Gu, Y.; Zheng, Y.; Ren, L.; Hu, Y.; Liang, A.; Peng, L.; Zhang, L.; Li, J.
Abstract: Objectives: We investigated whether long-term ambient air pollutants (AAP) exposure was associated with estimated glomerular filtration rate (eGFR) among hospitalized patients living in urban areas of Shanghai, China. Study design: This was a cross-sectional observational study. Methods: A total of 3622 newly hospitalized inpatients were investigated from October 2014 to May 2015. The prior year's average exposure to particulate matter (PM) of each participant was estimated using the Kriging interpolation method of ArcGIS. The estimated eGFR was calculated according to the chronic kidney disease epidemiology collaboration (CKD-EPI) equation. Both generalized linear and logistic regression models were applied to assess the associations between AAP and renal function. Results: One-year PM10 exposure was associated with lower eGFR; each standard deviation (SD) increase in PM10 was significantly associated with the increased prevalence of CKD [adjusted odds ratio (OR) 1.11; 95% confidence interval (CI): 1.02, 1.21], and lower eGFR by −0.40 (95%CI: −0.80, −0.01) ml/min/1.73 m 2 . Moreover, the effect of PM10 was significantly greater in people over 65 years old. Conclusion: Our results supported that exposure to ambient PM10 increased the risk of CKD and negatively affected renal function among Chinese adults. Highlights: We aim to evaluate the effect of long exposure to air pollutants on renal function among hospitalized patients in China. One-year PM10 exposure was associated with lower eGFRs and increased prevalence of CKD (chronic kidney disease). Patients over 65 years, males, patients with a BMI＜24 kg/m 2 and without hypertension might be vulnerable to the effect.